Aflatoxin B1 impairs leydig cells through inhibiting AMPK/mTOR-mediated autophagy flux pathway. (October 2019) - Chen, Xianwu; Li, Chao; Chen, Yong; Ni, Chaobo; Chen, Xiuxiu; Zhang, Linlei; Xu, Xuni; Chen, Min; Ma, Xinyi; Zhan, Huilu; Xu, Aoyu; Ge, Renshan; et al.
Abstract: Aflatoxin B1 (AFB1), a potential endocrine disrupter, has been shown to induce hepatotoxicity in animal models, but the effects of AFB1 on Leydig cell function are unclear. In this study, in vivo exposure to AFB1 at 15 and 150 μg/kg/day lowered serum testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) levels, reduced Leydig cell number, and down-regulated the expression of testosterone biosynthesis-related genes. In vitro study showed that AFB1 (10 μM) significantly increased ROS levels, and decreased T production in Leydig cells by suppressing certain T-biosynthesis gene expressions. Moreover, AFB1 induced Leydig cell apoptosis through lowering pAMPK/AMPK ratio and increasing pmTOR/mTOR ratio, and then further up-regulating autophagy and apoptosis proteins, LC3, BECLIN 1, and BAX, as well as down-regulating autophagy flux protein P62 and anti-apoptosis protein BCL-2. AFB1-induced toxicity in Leydig cells was characterized by inhibiting T-biosynthesis gene expression, reducing Leydig cell number, promoting ROS production, and inducing cell apoptosis via suppressing AMPK/mTOR-mediated autophagy flux pathway. Graphical abstract: Image 1 Highlights: Aflatoxin B1 down-regulates Leydig cell gene expression. Aflatoxin B1 decreases Leydig cell number. Aflatoxin B1 induces Leydig cell apoptosis by AMPK/mTOR-mediated autophagy flux pathway. Aflatoxin B1 induces Leydig cell ROS generation.